Esterification vs. 1,3-Dipolar Cycloaddition Synthetic Approaches for Preparation of the Fluorescently Labelled Iron(II) Clathrochelates - Selin, Roman A.; Chernii, Viktor Ya; Kryvorotenko, Dmytro; Mokhir, Andriy; Voloshin, Yan Z. (Journal Macroheterocycles, 2021)
Two most common synthetic approaches (i.e. the esterification and 1,3-dipolar cycloaddition reactions) to a functionalization of the reactive three-dimensional molecular platforms, allowing to obtain the fluorescently labelled iron(II) clathrochelates and, therefore, to study their localization and accumulation in cancer cells, were compared. Because an esterification approach gave the target complexes in a very low yield, if any, such a functionalization of a known propargylamine iron(II) clathrochelate complex with terminal C C bond as a reactive macrobicyclic precursor by the copper-promoted 1,3-dipolar cycloaddition "click" reaction was also tested. This one-pot synthetic procedure allowed to obtain the cumarin-terminated iron(II) cage complex in a high yield; it was characterized using elemental analysis, ESI-TOF mass, and H-1 and C-13H-1 NMR spectra.
CRIS-Team WoS Importer:2021-06-25